Analisis Perencanaan Dan Pelaksanaan Pengelolaan Keuangan Desa: (Studi pada Kantor Desa Kunir Kidul Kecamatan Kunir Kabupaten Lumajang) - Mimin Yatminiwati (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2018)
This study aims to describe the planning and implementation of village finances in the village of Kunir Kidul Kunir district Lumajang district. The object of this study is the Analysis of Village Finance Planning and Implementation by Permendagri No. 113 of 2014 on the management of village finances in the village of Kunir Kidul Kunir district Lumajang district. In this study, the authors used a type of qualitative research with case study approach. Data collection techniques used were interviews, observation and documentation. Data analysis technique used is an interactive analysis model that includes four components, namely data collection, data reduction, data presentation, and verification. The results showed that the planning and implementation of village financial management in Kunir Kidul village is in accordance with Permendagri No.113 of 2014 and the applicable Laws. This can be seen from the planning and implementation process from the beginning to the end, the process of preparing the budget plan, the preparation of activity plans and the implementation process is in accordance with the outcome plan of the meeting, reporting the use of finance with guidelines and procedures that have been determined through several stages and verification , as well as the publication of transparent financial statements.